A revision of the genus Photinopygus Chatzimanolis (Staphylinidae: Xanthopygina) - Chatzimanolis, Stylianos (Zootaxa, 2023)
The xanthopygine genus Photinopygus Chatzimanolis, 2021 is revised. An identification key along with distribution maps and illustrations of structural features are provided for all 30 species. Nine species are described as new: P. akrodontis Chatzimanolis new species, P. alloportokalis Chatzimanolis new species, P. assingi Chatzimanolis new species, P. chryselytros Chatzimanolis new species, P. cotopaxi Chatzimanolis new species, P. koptopeos Chatzimanolis new species, P. mexicanus Chatzimanolis new species, P. schedonapicalis Chatzimanolis new species, P. thafmasios Chatzimanolis new species. Xanthopygus elegans Bernhauer and Xanthopygus collaris Bernhauer are placed into synonymy with Staphylinus cyanelytrius Perty, new synonymy; Xanthopygus violaceipennis Bernhauer is placed into synonymy with Xanthopygus cyanipennis Sharp, new synonymy; Xanthopygus depressus Sharp is placed into synonymy with Staphylinus faustus Erichson, new synonymy; Xanthopygus violaceus Sharp and Xanthopygus puncticollis Sharp are placed into synonymy with Staphylinus haemorrhoidalis Germar, new synonymy; Xanthopygus nigripes Sharp and Xanthopygus alienus Bernhauer are placed into synonymy with Staphylinus tepidus Erichson, new synonymy; and Xanthopygus flohri Sharp is placed into synonymy with Xanthopygus viridipennis Sharp, new synonymy. Lectotypes are designated for 24 species: Philonthus mirabilis Erichson, Staphylinus calidus Erichson, Staphylinus chrysopygus Nordmann, Staphylinus chrysurus Nordmann, Staphylinus faustus Erichson, Staphylinus haemorrhoidalis Germar, Staphylinus hilaris Erichson, Staphylinus iopterus Erichson, Staphylinus janthinipennis Blanchard, Staphylinus pyraster Erichson, Staphylinus sapphirinus Erichson, Staphylinus tepidus Erichson, Xanthopygus apicalis Sharp, Xanthopygus chapareanus Scheerpeltz, Xanthopygus cyanipennis Sharp, Xanthopygus dimidiatus Bernhauer, Xanthopygus depressus Sharp, Xanthopygus puncticollis Sharp, Xanthopygus punctatus Bernhauer, Xanthopygus rufipennis Sharp, Xanthopygus solskyi Sharp, Xanthopygus violaceipennis Bernhauer, Xanthopygus violaceus Sharp, and Xanthopygus viridipennis Sharp. A neotype is designated for Staphylinus cyanelytrius Perty.